Venous Obstruction Following Pacemaker or Implantable Cardioverter-Defibrillator Implantation, Mini Review - Mohammad Ali Akbarzadeh (Publisher: Shahid Beheshti University of Medical Sciences, 2016)
Venous obstruction is relatively frequent following permanent pacemaker or implantable cardioverter-defibrillator (ICD) implantation. However, most of them are asymptomatic. Although the exact risk factor for this complication is not known, number of leads, heart failure and infection may prone the patient to this complication. The goal standard for detection of vein stenosis is venography; however, ultrasound sonography has an acceptable accuracy. Anticoagulant therapy may be considered for symptomatic patients. For device upgrading, non-functional leads removal, venoplasty and rarely surgical treatment may be indicated.